Anti-leishmanial effects of purified compounds from aerial parts of Baccharis uncinella C. DC. (Asteraceae) - Passero, Luiz Felipe D.; Bonfim-Melo, Alexis; Corbett, Carlos Eduardo P.; Laurenti, Marcia D.; Toyama, Marcos H. [UNESP]; de Toyama, Daniela O.; Romoff, Paulete; Favero, Oriana A.; dos Grecco, Simone S.; Zalewsky, Cynthia A.; Lago, Joo Henrique G. (Springer, 2011)
Species of Baccharis exhibit antibiotic, antiseptic, wound-healing, and anti-protozoal properties, and have been used in the traditional medicine of South America for the treatment of several diseases. In the present work, the fractionation of EtOH extract from aerial parts of Baccharis uncinella indicated that the isolated compounds caffeic acid and pectolinaringenin showed inhibitory activity against Leishmania (L.) amazonensis and Leishmania (V.) braziliensis promastigotes, respectively. Moreover, amastigote forms of both species were highly sensible to the fraction composed by oleanolic + ursolic acids and pectolinaringenin. Caffeic acid also inhibited amastigote forms of L. (L.) amazonensis, but this effect was weak in L. (V.) braziliensis amastigotes. The treatment of infected macrophages with these compounds did not alter the levels of nitrates, indicating a direct effect of the compounds on amastigote stages. The results presented herein suggest that the active components from B. uncinella can be important to the design of new drugs against American tegumentar leishmaniases.